Secondary battery, electric device, artificial graphite and preparation method thereof

By using artificial graphite on the surface and center part in the secondary battery and adjusting its crystal plane spacing and specific surface area, the shortcomings of existing secondary batteries in the first Coulomb efficiency and storage performance are solved, and higher battery efficiency and stability are achieved.

CN119852316APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410969163.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing secondary batteries have shortcomings in the efficiency and storage performance of the first Coulombs, making it difficult to meet the needs of efficient energy storage.

Method used

Artificial graphite including surface part and center part is used as the negative electrode material. By adjusting the crystal plane spacing and specific surface area of ​​graphite, the diffusion resistance and side reaction of active ions are reduced, and the stability and efficiency of the battery are improved.

Benefits of technology

It significantly improves the first-time Coulomb efficiency and storage performance of secondary batteries, improves the stability of negative electrode active substances and the energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852316A_ABST
    Figure CN119852316A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery, an electric device, artificial graphite and a preparation method thereof. The secondary battery comprises a negative electrode piece, the negative electrode piece comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer comprises artificial graphite, the artificial graphite comprises a surface part and a central part, the surface part is continuously or discontinuously distributed in the central part, the interplanar spacing D002 of the surface part is larger than the interplanar spacing D002 of the central part, and the interplanar spacing D002 of the surface part is larger than the interplanar spacing D002 of the central part. And the interplanar spacing D002 is the interlayer spacing of the graphite 002 crystal face. The secondary battery of the negative pole piece has improved first coulombic efficiency and storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery, an electrical device, artificial graphite and a preparation method thereof. Background Art

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields.

[0003] With the application and promotion of secondary batteries, people have higher and higher requirements on the first coulombic efficiency and storage performance of secondary batteries. How to improve the first coulombic efficiency and storage performance of batteries has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery, an electrical device, artificial graphite and a preparation method thereof. The secondary battery has an improved first coulombic efficiency and storage performance.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a secondary battery, which includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer includes artificial graphite, the artificial graphite includes a surface portion and a central portion, the surface portion is continuously or discontinuously distributed in the central portion, the interplanar spacing D002 of the surface portion is greater than the interplanar spacing D002 of the central portion, wherein the interplanar spacing D002 is the interlayer spacing of the graphite 002 crystal plane. Providing a surface portion with a relatively large interplanar spacing outside the central portion of graphite can increase the interlamellar spacing of graphite, reduce the diffusion resistance of active ions, thereby improving the stability of negative electrode active materials, and thus helping to improve the storage performance of the battery. In addition, the provision of the surface portion is conducive to reducing the specific surface area of ​​artificial graphite, reducing the side reactions of artificial graphite and electrolyte, and thus reducing the loss of active ions during the first cycle, thereby further improving the first coulomb efficiency of the battery.

[0006] In some embodiments, the interplanar spacing D002 of the surface portion is 0.345 nm to 0.355 nm. By controlling the interplanar spacing D002 of the surface portion within the above range, it is further beneficial to improve the stability of the material and obtain a graphite material with a high gram capacity.

[0007] In some embodiments, the interplanar spacing D002 of the center portion is 0.335 nm to 0.345 nm. By controlling the interplanar spacing D002 of the center portion within the above range, it is beneficial to improve the energy density of the battery.

[0008] In some embodiments, the artificial graphite satisfies at least one of the following:

[0009] (1) The BET specific surface area of ​​artificial graphite is 0.6 m 2 / g to 1.4m 2 / g;

[0010] (2) I of artificial graphite D / I G The value is 0.05 to 0.15, where I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at

[0011] (3) The volume average particle size Dv50 of the artificial graphite is 12 μm to 22 μm;

[0012] (4) The powder compaction density of artificial graphite at 50,000 N is 1.93 g / cc to 2.15 g / cc;

[0013] (5) The gram capacity of artificial graphite is 355 mAh / g to 365 mAh / g.

[0014] In some embodiments, the artificial graphite has a BET specific surface area of ​​0.85 m 2 / g to 1.18m 2 / g. By controlling the BET specific surface area of ​​artificial graphite within the above range, it is beneficial to further improve the first coulombic efficiency of the battery.

[0015] In some embodiments, the artificial graphite D / I G The value is 0.067 to 0.087. D / I G Controlling the value within the above range is beneficial for the secondary battery to maintain a higher energy density and high capacity.

[0016] A second aspect of the present application provides an electrical device, comprising the secondary battery of the first aspect.

[0017] The third aspect of the present application provides an artificial graphite, the artificial graphite includes a surface portion and a central portion, the surface portion is continuously or discontinuously distributed in the central portion, and the interplanar spacing D002 of the surface portion is greater than the interplanar spacing D002 of the central portion. The surface portion with a relatively large interplanar spacing is arranged on the surface of the central portion, which can increase the interlamellar spacing of the graphite and reduce the diffusion resistance of the active ions, thereby improving the cycle stability of the negative electrode active material, which is beneficial to the improvement of the battery storage performance. In addition, the setting of the surface portion can reduce the specific surface area of ​​the artificial graphite, reduce the side reactions of the artificial graphite and the electrolyte, and then reduce the loss of active ions (for example, active ions) during the first cycle, thereby improving the first coulomb efficiency of the battery.

[0018] In some embodiments, the interplanar spacing D002 of the surface portion is 0.345 nm to 0.355 nm. By controlling the interplanar spacing D002 of the surface portion within the above range, it is further beneficial to improve the stability of the material and obtain a graphite material with a high gram capacity.

[0019] In some embodiments, the interplanar spacing D002 of the center portion is 0.335 nm to 0.345 nm. By controlling the interplanar spacing D002 of the center portion within the above range, it is beneficial to further improve the energy density of the battery.

[0020] In some embodiments, the artificial graphite satisfies at least one of the following:

[0021] (1) The BET specific surface area of ​​artificial graphite is 0.6 m 2 / g to 1.4m 2 / g;

[0022] (2) I of artificial graphite D / I G The value is 0.05 to 0.15, where I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at .

[0023] The fourth aspect of the present application provides a method for preparing artificial graphite, comprising: mixing a binder and an artificial graphite precursor, and then granulating to obtain a first mixture; performing a first heat treatment on the first mixture to obtain a second mixture; mixing the second mixture and a carbon-containing additive to obtain a third mixture; performing a second heat treatment on the third mixture to obtain artificial graphite, wherein the artificial graphite comprises a surface portion and a central portion, the surface portion is continuously or discontinuously distributed in the central portion, the crystal plane spacing D002 of the surface portion is greater than the crystal plane spacing D002 of the central portion, wherein the crystal plane spacing D002 is the interlayer spacing of the graphite 002 crystal plane.

[0024] In the preparation method of the present application, by coating the surface of the second mixture with a carbon-containing additive before the second heat treatment, the oxygen loss of the second mixture during the second heat treatment can be reduced, and the defects of the surface / bulk of the second mixture can be repaired, so that the obtained material has fewer defects and a lower BET specific surface area. At the same time, during the second heat treatment, the carbon-containing additive itself can be rearranged to form a graphite material with a continuous lattice structure, thereby reducing the side reactions of the obtained material with the electrolyte. The artificial graphite prepared by this method as a negative electrode material can improve the first coulomb efficiency and storage performance of the battery.

[0025] In some embodiments, the artificial graphite precursor includes one or more of calcined coke, petroleum non-needle coke, petroleum needle coke, coal non-needle coke, and coal needle coke. The selection of the artificial graphite precursor is conducive to improving the energy density of the obtained artificial graphite.

[0026] In some embodiments, the artificial graphite precursor includes calcined coke. Selecting calcined coke as the artificial graphite precursor is beneficial to further improve the energy density of the obtained artificial graphite.

[0027] In some embodiments, the carbon-containing additive includes at least one of solid asphalt, liquid asphalt, and polyacrylonitrile. The carbon-containing additive is a material that can be graphitized at high temperature, and the use of the carbon-containing additive is conducive to forming a surface portion with a suitable interplanar spacing.

[0028] In some embodiments, the carbon-containing additive includes liquid asphalt. Using liquid asphalt as the carbon-containing additive is conducive to uniform coating of the carbon-containing additive on the surface of the second mixture, thereby further reducing defects of the obtained material and reducing the BET specific surface area of ​​the obtained material.

[0029] In some embodiments, the coking value of the liquid asphalt is 10% to 20%. Liquid asphalt with a coking value of 10% to 20% has suitable heating stability, adhesion and aging performance for the present application, can effectively form a surface portion with a suitable interplanar spacing on the surface of the center portion, and is conducive to processing.

[0030] In some embodiments, the amount of the carbon-containing additive added is less than 10% compared to the mass of the artificial graphite precursor. By controlling the amount of the carbon-containing additive added within the above range, it is beneficial to maintain a high gram capacity of the obtained artificial graphite.

[0031] In some embodiments, the amount of the carbon-containing additive added is 0.5% to 6% relative to the mass of the artificial graphite precursor. By controlling the amount of the carbon-containing additive added within the above range, it is beneficial for the artificial graphite to maintain a high gram capacity.

[0032] In some embodiments, the first heat treatment includes pre-carbonization at 1000° C. to 1500° C. By performing the first heat treatment under such conditions, the organic matter in the precursor undergoes a carbonization reaction to form a carbonaceous structure, which is beneficial for the material to obtain higher conductivity and better mechanical stability.

[0033] In some embodiments, the second heat treatment includes graphitization at 2800° C. to 3200° C. The second heat treatment under such conditions is conducive to promoting the growth of graphite grains, and finally obtaining artificial graphite with suitable interplanar spacing, and the obtained artificial graphite has a higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0035] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0036] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0037] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0038] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0039] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0040] Figure 7 This is a transmission electron microscope TEM image of the artificial graphite of Example 1 of the present application.

[0041] Description of reference numerals:

[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0043] Hereinafter, the embodiments of the secondary battery, the electrical device, the artificial graphite and the preparation method thereof of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0047] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0048] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0049] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0050] Artificial graphite is a graphite material prepared by chemical or physical methods. Artificial graphite has the advantages of high powder compaction density and high gram capacity, so it is widely used as the negative electrode material of secondary batteries.

[0051] A large number of defects (for example, defects caused by the crushing process) are introduced during the preparation of artificial graphite, which makes it easy for artificial graphite to react with the electrolyte when used as a negative electrode material, thereby consuming the active ions inside the battery, reducing the battery's first coulombic efficiency and deteriorating the battery's storage performance.

[0052] It has been reported that after graphitization, graphite particles are coated with asphalt and carbonized to form a layer of amorphous carbon on the surface of the graphite particles. The amorphous carbon can repair the surface / bulk defects of the graphite particles.

[0053] The above method can reduce the specific surface area of ​​artificial graphite to a certain extent, reduce the side reactions between artificial graphite and electrolyte, and improve the initial coulombic efficiency and storage performance of the battery. However, the reduction degree of the specific surface area of ​​artificial graphite is limited, and the surface part is an amorphous carbon layer, which has high activity and low capacity. There are many side reactions between the surface part and the electrolyte, which limits the improvement of the initial coulombic efficiency and storage performance of the battery.

[0054] Based on this, the present application proposes a secondary battery, an electrical device, artificial graphite and a preparation method thereof. The secondary battery has an improved first coulombic efficiency and storage performance. The present invention and optional embodiments are described in more detail below.

[0055] Secondary battery

[0056] A first aspect of the present application provides a secondary battery.

[0057] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.

[0058] The secondary battery of the present application includes a negative electrode plate, which includes a negative electrode collector and a negative electrode film layer located on at least one surface of the negative electrode collector, and the negative electrode film layer includes artificial graphite, and the artificial graphite includes a surface portion and a central portion, the surface portion is continuously or discontinuously distributed in the central portion, and the crystal plane spacing D002 of the surface portion is greater than the crystal plane spacing D002 of the central portion, wherein the crystal plane spacing D002 is the interlayer spacing of the graphite 002 crystal plane.

[0059] In the present application, interplanar spacing refers to the distance between two lattices in the periodic configuration structure of a crystal, which is measured as follows: using Pt nanoparticles as a substrate, a Thermo Scientific-Talos F200SG2 field emission transmission electron microscope (TEM) is used for high-resolution testing under bright field: after adjusting the test interface to be clear, the graphite particles are located based on the difference in contrast between the Pt nanoparticles and the graphite particles, and the corresponding area is selected. The fringe image is obtained by fast Fourier transform (FFT), and the fringe spacing is obtained by software measurement, which corresponds to the interplanar spacing.

[0060] Arranging a surface portion with a relatively large interplanar spacing outside the central portion of graphite can increase the interlamellar spacing of graphite and reduce the diffusion resistance of active ions, thereby improving the stability of the negative electrode active material, and thus facilitating the improvement of the storage performance of the battery. In addition, the arrangement of the surface portion is conducive to reducing the specific surface area of ​​artificial graphite and reducing the direct contact between artificial graphite and electrolyte, thereby reducing the side reactions between the two, thereby reducing the loss of active ions during the first cycle and improving the first coulombic efficiency of the battery.

[0061] In some embodiments, the thickness of the surface portion is less than or equal to 0.5 nm. Accordingly, when measuring the interplanar spacing of the surface portion, a region within the range of 0 to 0.5 nm in contact with the Pt nanoparticles is usually selected, and then a fringe image is obtained by Fourier transformation, and the interplanar spacing of the surface portion is obtained by measuring with software.

[0062] In some embodiments, the interplanar spacing D002 of the surface portion is 0.345nm to 0.355nm, optionally, 0.346nm to 0.352nm. For example, the interplanar spacing D002 of the surface portion is 0.345nm, 0.346nm, 0.347nm, 0.349nm, 0.350nm, 0.351nm, 0.352nm, 0.355nm or a value between the ranges of any two of these values. By controlling the interplanar spacing D002 of the surface portion within the above range, it is further beneficial to improve the stability of the material and obtain a graphite material with a high gram capacity.

[0063] In some embodiments, the interplanar spacing D002 of the center portion is 0.335nm to 0.345nm. For example, the interplanar spacing D002 of the center portion is 0.335nm, 0.336nm, 0.339nm, 0.342nm, 0.345nm or a value between any two of these values. Wherein, in the measurement of the interplanar spacing of the center portion, sampling is usually performed at a region extending about 50nm or more from the sampling point of the surface portion to the center, and then a fringe image is obtained by fast Fourier transform, and the interplanar spacing of the center portion is obtained by software measurement.

[0064] By controlling the interplanar spacing D002 of the center portion within the above range, it is beneficial to improve the energy density of the battery.

[0065] In some embodiments, the ratio of the mass of the surface portion to the mass of the center portion is less than or equal to 2:100. The ratio of the mass of the surface portion to the mass of the center portion is 0.075:100, 0.45:100, 0.9:100, 2:100, or a value between the ranges formed by any two of these values. By controlling the ratio of the mass of the surface portion to the mass of the center portion within the above range, it is beneficial to reduce the specific surface area of ​​the negative electrode active material, while helping the negative electrode active material maintain a higher gram capacity.

[0066] In some embodiments, the artificial graphite satisfies at least one of the following:

[0067] (1) The BET specific surface area of ​​artificial graphite is 0.6 m 2 / g to 1.4m 2 / g, optionally, a BET specific surface area of ​​0.85m 2 / g to 1.2m 2 / g, optionally, the BET specific surface area of ​​artificial graphite is 0.9m 2 / g to 1.2m 2 / g, optionally, the BET specific surface area of ​​artificial graphite is 0.85m 2 / g to 1.18m 2 / g, for example, the BET specific surface area of ​​artificial graphite is 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.85m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.26m 2 / g, 1.3m 2 / g, 1.4m 2 / g or a value between the ranges formed by any two of these values. By controlling the BET specific surface area of ​​artificial graphite within the above range, it is beneficial to further improve the first coulombic efficiency of the battery.

[0068] (2) I of artificial graphite D / I G The value is 0.05 to 0.15, where I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at D / I G 0.067 to 0.096, optionally I D / I G is 0.067 to 0.087, for example, I D / I G is 0.05, 0.067, 0.081, 0.10, 0.15 or a range consisting of any two of these values. D / I G The value is controlled within the above range, which is beneficial for the secondary battery to maintain a high energy density. (3) The volume average particle size Dv50 of the artificial graphite is 12 μm to 22 μm, and optionally, the volume distribution average particle size Dv50 is 16.1 μm to 16.5 μm, for example, the volume average particle size Dv50 of the artificial graphite is 12 μm, 14 μm, 16 μm, 16.1 μm, 16.5 μm, 18 μm, 20 μm, 22 μm or a value between the ranges consisting of any two of these values.

[0069] (4) The powder compaction density of the artificial graphite at 50,000 N is 1.93 g / cc to 2.15 g / cc. For example, the powder compaction density of the artificial graphite at 50,000 N is 1.93 g / cc, 1.94 g / cc, 1.95 g / cc, 1.96 g / cc, 2.00 g / cc, 2.05 g / cc, 2.10 g / cc, 2.15 g / cc, or a value within a range consisting of any two of these values.

[0070] (5) The gram capacity of the artificial graphite is 355 mAh / g to 365 mAh / g, optionally, the gram capacity is 360.4 mAh / g to 362.1 mAh / g, for example, the gram capacity of the artificial graphite is 355 mAh / g, 356 mAh / g, 357 mAh / g, 358 mAh / g, 359 mAh / g, 360 mAh / g, 360.4 mAh / g, 361 mAh / g, 362 mAh / g, 362.1 mAh / g, 363 mAh / g, 364 mAh / g, 365 mAh / g or a value within a range consisting of any two of these values.

[0071] In the present application, the BET specific surface area of ​​artificial graphite is the total area of ​​the material per unit mass, which can be measured by instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0072] In this application, the I of artificial graphite D / I G The Raman spectrum of the material is 1350±50cm -1 The D peak intensity at 1580±50cm -1 The ratio of the G peak intensity at 100 points can be used to characterize the defect degree and graphitization degree in the material. It can be tested using a Raman spectrometer. The test conditions are: excitation wavelength of 532nm, grating of 600 lines, objective lens of 50 times, integration time of 10s, accumulation times of 3 times, surface scanning, and obtaining the D peak and G peak intensities of 100 points. Calculate the I of 100 points. D / I G , remove the largest and smallest 30 I D / I G The average value of the remaining 40 points is the I D / I GThe testing instrument may be a Horiba LabRAM HR800 Raman spectrometer.

[0073] In the present application, the compacted density of artificial graphite powder is the mass per unit volume of the powder material after being compressed under a certain pressure (e.g., 50,000 N), which can be measured by instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (e.g., UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009.

[0074] In the present application, the gram capacity of artificial graphite refers to the amount of electrical energy stored per unit mass of artificial graphite, which can be measured using instruments and methods known in the art. For details, please refer to the test method described in the following embodiments.

[0075] In some embodiments, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0076] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0077] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0078] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0079] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0080] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material (artificial graphite), the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0081] Secondary battery

[0082] A second aspect of the embodiments of the present application provides a secondary battery. The secondary battery of the present application will be described below with reference to the accompanying drawings as appropriate.

[0083] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.

[0084] Generally, a secondary battery cell also includes a positive electrode, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0085] Positive electrode

[0086] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.

[0087] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0088] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0089] In some embodiments, when the battery cell is a lithium secondary battery, the positive electrode active material may adopt a positive electrode active material for lithium secondary batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0090] In some embodiments, when the battery cell is a sodium secondary battery, the positive electrode active material may be a positive electrode active material for a sodium secondary battery known in the art. As an example, the positive electrode active material may include sodium transition metal oxides, polyanionic compounds, Prussian blue compounds, and the like.

[0091] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0092] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0093] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0094] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0095] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0096] Electrolytes

[0097] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0098] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0099] In some embodiments, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0100] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0101] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0102] Isolation film

[0103] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0104] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0105] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0106] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0107] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0108] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0109] In some embodiments, reference Figure 2, the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0110] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0111] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0112] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0113] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0114] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0115] Electrical devices

[0116] A second aspect of the present application provides an electrical device, and the electrical device of the present application will be described below with reference to the accompanying drawings as appropriate.

[0117] The electrical device mentioned in the embodiments of the present application includes the secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0118] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0119] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0120] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0121] Artificial graphite

[0122] A third aspect of the present application provides an artificial graphite, which includes a surface portion and a central portion, wherein the surface portion is continuously or discontinuously distributed in the central portion, and the inter-crystalline spacing D002 of the surface portion is greater than the inter-crystalline spacing D002 of the central portion.

[0123] Arranging a surface portion with a relatively large interplanar spacing on the surface of the central portion of graphite can increase the interlamellar spacing of graphite and reduce the diffusion resistance of active ions, thereby improving the cycle stability of the negative electrode active material and facilitating the improvement of battery storage performance. In addition, the arrangement of the surface portion can reduce the specific surface area of ​​artificial graphite, reduce the side reaction between artificial graphite and electrolyte, and further reduce the loss of active ions (e.g., active ions) during the first cycle, thereby improving the first coulomb efficiency of the battery.

[0124] In some embodiments, the interplanar spacing D002 of the surface portion is 0.345 nm to 0.355 nm. By controlling the interplanar spacing D002 of the surface portion within the above range, it is beneficial to improve the stability of the material and obtain a graphite material with a high gram capacity.

[0125] In some embodiments, the interplanar spacing D002 of the center portion is 0.335 nm to 0.345 nm. By controlling the interplanar spacing D002 of the center portion within the above range, it is beneficial to further improve the energy density of the battery.

[0126] In some embodiments, the artificial graphite satisfies at least one of the following:

[0127] (1) The BET specific surface area of ​​artificial graphite is 0.6 m 2 / g to 1.4m 2 / g, optionally, a BET specific surface area of ​​0.85m 2 / g to 1.26m 2 / g, optionally, the BET specific surface area of ​​artificial graphite is 0.9m 2 / g to 1.2m 2 / g, for example, the BET specific surface area of ​​artificial graphite is 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.85m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.26m 2 / g, 1.3m 2 / g, 1.4m 2 / g or a value within a range consisting of any two of these values.

[0128] (2) I of artificial graphite D / I G The value is 0.05 to 0.15, where I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at D / I G is 0.067 to 0.096, optionally, I D / I G is 0.067 to 0.087, for example, I D / I G It is 0.05, 0.067, 0.081, 0.10, 0.15 or a range consisting of any two of these values.

[0129] (3) The volume average particle size Dv50 of the artificial graphite is 12 μm to 22 μm, optionally, the volume average particle size Dv50 is 16.1 μm to 16.5 μm, for example, the volume average particle size Dv50 of the artificial graphite is 12 μm, 14 μm, 16 μm, 16.1 μm, 16.5 μm, 18 μm, 20 μm, 22 μm or a value within a range consisting of any two of these values.

[0130] (4) The powder compaction density of the artificial graphite at 50,000 N is 1.93 g / cc to 2.15 g / cc. For example, the powder compaction density of the artificial graphite at 50,000 N is 1.93 g / cc, 1.94 g / cc, 1.95 g / cc, 1.96 g / cc, 2.00 g / cc, 2.05 g / cc, 2.10 g / cc, 2.15 g / cc, or a value within a range consisting of any two of these values.

[0131] (5) The gram capacity of the artificial graphite is 355 mAh / g to 365 mAh / g, optionally, the gram capacity is 360.4 mAh / g to 362.1 mAh / g, for example, the gram capacity of the artificial graphite is 355 mAh / g, 356 mAh / g, 357 mAh / g, 358 mAh / g, 359 mAh / g, 360 mAh / g, 360.4 mAh / g, 361 mAh / g, 362 mAh / g, 362.1 mAh / g, 363 mAh / g, 364 mAh / g, 365 mAh / g or a value within a range consisting of any two of these values.

[0132] Preparation method of artificial graphite

[0133] The fourth aspect of the present application provides a method for preparing artificial graphite, which comprises steps (1) to (4).

[0134] Step (1): mixing a binder and an artificial graphite precursor, and then granulating to obtain a first mixture.

[0135] In the present application, artificial graphite precursor refers to a raw material for synthesizing artificial graphite. The present application does not specifically limit the type of artificial graphite precursor, and artificial graphite precursors known in the art can be used. For example, the artificial graphite precursor includes one or more of calcined coke, petroleum non-needle coke, petroleum needle coke, coal non-needle coke, and coal needle coke. The selection of the above-mentioned artificial graphite precursor is conducive to improving the energy density of the obtained artificial graphite.

[0136] In some embodiments, the artificial graphite precursor includes calcined coke. Selecting calcined coke as the artificial graphite precursor is beneficial to further improve the energy density of the obtained artificial graphite.

[0137] In some embodiments, the artificial graphite precursor includes calcined coke, which includes coke formed by calcining the above-mentioned petroleum-based non-needle coke, petroleum-based needle coke, coal-based non-needle coke, and coal-based needle coke.

[0138] In some embodiments, the calcined coke is pulverized to facilitate mixing of the calcined coke with a binder.

[0139] In some embodiments, the crushed calcined coke is shaped and graded to obtain an artificial graphite precursor with a suitable volume average particle size DV50. The present application does not specifically limit the shaping and grading methods, and the shaping and grading methods known in the art can be used.

[0140] The present application does not specifically limit the type of the binder, and any binder known in the art may be used. For example, the binder may include solid asphalt, liquid asphalt, and the like.

[0141] In the present application, solid asphalt refers to asphalt that is solid at room temperature, and liquid asphalt refers to asphalt that is liquid at room temperature.

[0142] The present application does not specifically limit the implementation method of granulation, and any granulation method known in the art can be used.

[0143] Step (2): performing a first heat treatment on the first mixture to obtain a second mixture.

[0144] In some embodiments, the first heat treatment includes a pre-carbonization treatment at 1000° C. to 1500° C. for 2 h to 4 h. By performing the first heat treatment under such conditions, the organic matter in the precursor undergoes a carbonization reaction to form a carbonaceous structure, which is beneficial for the material to obtain higher conductivity and better mechanical stability.

[0145] Step (3): mixing the second mixture and the carbon-containing additive to obtain a third mixture.

[0146] The present application does not specifically limit the type of carbon-containing additives, and carbon-containing substances known in the art can be used.

[0147] The purpose of mixing the second mixture (e.g., carbonized particles) with the carbon-containing additive is to coat the surface of the second mixture with the carbon-containing additive so that during the subsequent second heat treatment, the carbon material in the carbon-containing additive can be transferred to the surface / bulk of the second mixture, repairing the defects of the surface / bulk of the second mixture, reducing the BET specific surface area of ​​the artificial graphite, reducing the direct contact between the obtained material and the electrolyte, thereby reducing the side reactions between the two, and further reducing the loss of active ions during the first cycle, and improving the first coulombic efficiency of the battery. In addition, during the second heat treatment, the carbon-containing additive itself can be rearranged to form a graphite material with a continuous lattice structure, which is beneficial for the graphite material to maintain a higher gram capacity.

[0148] In some embodiments, the carbon-containing additive includes at least one of solid asphalt, liquid asphalt, and polyacrylonitrile. The carbon-containing additive is a material that can be graphitized at high temperature, and the use of the carbon-containing additive is conducive to forming a surface portion with a suitable interplanar spacing.

[0149] In some embodiments, the carbon-containing additive includes liquid asphalt. Liquid asphalt is more easily mixed with the second mixture, which is conducive to uniform coating of the carbon-containing additive on the surface of the second mixture, so that the formed surface portion is continuously distributed on the central portion, thereby further reducing defects of the obtained material and reducing the BET specific surface area of ​​the obtained material.

[0150] In some embodiments, the coking value of liquid asphalt is 10% to 20%. For example, the coking value of liquid asphalt is 10%, 11%, 12%, 13%, 14%, 15% or a value between the range of any two of these values. The "coking value" in asphalt refers to the content of combustible substances in asphalt, mainly referring to the content of hydrocarbon substances with a high hydrogen content. During the processing, storage, transportation and use of asphalt, the higher the content of combustible substances in asphalt, the worse its stability is, and it is easy to oxidize and crack, so that the asphalt is damaged during use and loses its original performance. The calculation formula of the coking value of asphalt is: coking value (%) = (initial mass-residue mass) / initial mass × 100%; wherein, the initial mass refers to the mass of the original asphalt after drying to normal weight; the residue mass refers to the mass remaining when the dried asphalt is heated to 180°C under specific conditions. It can usually be determined by conventional methods such as thermogravimetric analysis and infrared spectroscopy. Asphalts with different coking values ​​are commercially available. In the present application, the liquid asphalt with a coking value of 10% to 20% has appropriate heating stability, adhesion and aging properties, can effectively form a surface portion with a suitable interplanar spacing on the surface of the center portion, and is conducive to processing.

[0151] In some embodiments, the amount of the carbon-containing additive added is less than 10% compared to the mass of the artificial graphite precursor, optionally, the amount added is 0.5% to 6%, the amount added is 0.5 to 3%, the amount added is 4 to 6%, the amount added is 1% to 4%, and the amount added is 2% to 4%. For example, the amount of the carbon-containing additive added is 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, or a value between the ranges of any two of these values. By controlling the amount of the carbon-containing additive added within the above range, it is beneficial for the obtained artificial graphite to maintain a high gram capacity.

[0152] In some embodiments, the surface carbon residue after the secondary heat treatment can be used as the mass of the middle surface of the artificial graphite, wherein the surface carbon residue can be calculated by the following formula: surface carbon residue = liquid asphalt addition amount * liquid asphalt coking value.

[0153] In some embodiments, the carbon-containing additive includes liquid asphalt with a coking value of 15%, and the amount of the carbon-containing additive added is 0.5% to 3%. The surface residual carbon amount is calculated by the following formula: surface residual carbon amount = liquid asphalt addition amount * 15%, and the surface residual carbon amount is obtained to be 0.075% to 0.45%, and the BET specific surface area of ​​the obtained artificial graphite is 0.90m 2 / g to 1.2m 2 / g.

[0154] In some embodiments, the carbon-containing additive includes liquid asphalt with a coking value of 15%, and the amount of the carbon-containing additive added is 3% to 6%, which is calculated by the following formula: surface residual carbon amount = liquid asphalt addition amount * 15%, and the surface residual carbon amount is obtained to be 0.45% to 0.9%, and the specific surface area of ​​the obtained artificial graphite is 0.65m 2 / g to 1.05m 2 / g.

[0155] Step (4): performing a second heat treatment on the third mixture to obtain artificial graphite, wherein the artificial graphite includes a central portion and a surface portion arranged on at least a portion of the surface of the central portion, and the interplanar spacing D002 of the surface portion is greater than the interplanar spacing D002 of the central portion.

[0156] In some embodiments, the second heat treatment includes a graphitization treatment to allow the carbon material of the carbon-containing additive to rearrange to form a graphite material having a continuous graphite lattice.

[0157] In some embodiments, the second heat treatment includes graphitization treatment at 2800° C. to 3200° C. for 5 to 10 days, for example. By performing the second heat treatment under such conditions, the growth of graphite grains is promoted, and artificial graphite with a suitable interplanar spacing is finally obtained, and the artificial graphite obtained has a higher energy density.

[0158] In the preparation method of the present application, by coating the surface of the second mixture with a carbon-containing additive before the second heat treatment, the oxygen loss of the second mixture during the second heat treatment can be reduced, and the defects of the surface / bulk of the second mixture can be repaired, so that the obtained material has fewer defects and a lower BET specific surface area, thereby reducing the side reactions of the obtained material with the electrolyte. The artificial graphite prepared by this method can be used as a negative electrode material to improve the first coulomb efficiency and storage performance of the battery. At the same time, during the second heat treatment, the carbon-containing additive itself can be rearranged to form a graphite material with a continuous lattice structure, which is beneficial for the graphite material to maintain a higher gram capacity.

[0159] Example

[0160] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0161] Example 1

[0162] Preparation of artificial graphite

[0163] The crushed calcined coke was shaped and classified to obtain an artificial graphite precursor (precursor I) with a volume average particle size DV50 of 11.0 μm.

[0164] The precursor I and the binder (solid asphalt with a softening point of 200° C.) were mixed in a mass ratio of 100:10, and then granulated to obtain a first mixture (granulated product).

[0165] The granulated product was subjected to a first heat treatment (pre-carbonization treatment) at 1150° C. for 2 h to obtain a second mixture (precursor II) having a volume average particle size DV50 of 16.1 μm.

[0166] Precursor II was mixed with a carbon-containing additive (liquid asphalt with a coking value of 15%) at a mass ratio of 100:2 to obtain a third mixture.

[0167] The third mixture is subjected to a second heat treatment (graphitization treatment) at 3000° C. for 7 days, and then subjected to demagnetization and screening treatments to obtain artificial graphite.

[0168] Determination of artificial graphite parameters

[0169] (1) Test of the interplanar spacing D002 of the surface / center:

[0170] After the artificial graphite prepared in Example 1 was pre-treated by focused ion beam (FIB) thinning, Pt nanoparticles were used as the substrate and high-resolution testing was performed using a Thermo Scientific-Talos F200S G2 field emission transmission electron microscope (TEM). During the test, samples were taken in the area in contact with Pt (as surface data), and samples were taken from the area extending about 50 nm from the sampling point to the center (as center data). The instrument automatically performed fast Fourier transform (FFT) to obtain a fringe image, and the lattice spacing of the surface part and the crystal plane spacing of the center part were respectively obtained by measuring the software. The test results can be seen in Figure 7 .

[0171] Figure 7 (1) is a TEM image of the surface of artificial graphite obtained in Example 1. Figure 7 (2) in Figure 7 The Fourier transform result of (1) in FIG. 1 shows that the interplanar spacing of the 002 crystal planes in the surface part is 0.350 nm.

[0172] Figure 7 (3) is a TEM image of the center of the artificial graphite of Example 1. Figure 7 (4) in is Figure 7 Figure (3) shows the Fourier transform result. It can be seen that the interplanar spacing of the 002 crystal plane in the center is about 0.342nm.

[0173] (2) BET specific surface area test:

[0174] Referring to GB / T 19587-2017, the nitrogen adsorption specific surface area analysis (Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA) was used for testing, and the BET method was used for calculation. The BET specific surface area of ​​the artificial graphite prepared in Example 1 was 1.02 m 2 / g.

[0175] (3) Test of volume average particle size Dv50:

[0176] According to the particle size distribution laser diffraction method of GB / T 19077-2016, the average particle size of the artificial graphite prepared in Example 1 is 16.3 μm.

[0177] (4) Test of powder compaction density under 50000N:

[0178] Weigh 1 g of the artificial graphite of Example 1 and add a 2 The mold was pressurized to 5000 kg (equivalent to 50000 N), maintained for 30 seconds, then released and maintained for 10 seconds, and then the powder compaction density of the artificial graphite in Example 1 under a pressure of 50000 N was recorded and calculated to be 1.96 g / cc.

[0179] (5)I D / I G The test:

[0180] Raman spectrometer (Horiba LabRAM HR800 Raman spectrometer) was used for testing. The test conditions were as follows: excitation wavelength of 532 nm, grating of 600 lines, objective of 50 times, integration time of 10 s, accumulation of 3 times, surface scanning, and 100 points of D peak (Raman spectrum at 1350 ± 50 cm -1 )Intensity ID , G peak (Raman spectrum at 1580±50cm -1 )Intensity I G , calculate I for 100 points D / I G , remove the largest and smallest 30 I D / I G The average value of the remaining 40 points, 0.075, is the I of the artificial graphite obtained in Example 1. D / I G .

[0181] Preparation of button cells

[0182] The artificial graphite prepared in Example 1, the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of ionized water at a mass ratio of 96.4:1:1.2:1.4 to form a negative electrode slurry.

[0183] The prepared slurry is coated on the surface of the negative electrode current collector copper foil and placed in a vacuum drying oven for drying. A metal lithium sheet is used as the counter electrode and a 12 μm polyethylene (PE) film is used as the isolation membrane. The electrolyte prepared above is assembled into a button cell in an argon-protected glove box.

[0184] Gram Capacity Test

[0185] At 25°C, the button cell prepared in Example 1 was first discharged at a constant current of 0.15 mA to 0.005 V, left to stand for 5 minutes, and then discharged at a constant current of 10 μA to 0.005 V, and the first-cycle discharge capacity of the button cell was recorded; thereafter, the button cell was charged at a constant current of 0.3 mA to 2.0 V, and the first-cycle charging capacity of the button cell was recorded. The ratio of the charging capacity to the mass of the artificial graphite is the gram capacity of the artificial graphite.

[0186] Preparation of secondary batteries

[0187] (1) Preparation of positive electrode sheet:

[0188] Lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and then solvent N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.

[0189] (2) Preparation of negative electrode sheet:

[0190] Artificial graphite, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are mixed in a proper amount of solvent deionized water in a mass ratio of 96.4:1:1.2:1.4 to form a negative electrode slurry. The negative electrode slurry is applied on the negative electrode current collector copper foil by extrusion coating, and after drying and cold pressing, a negative electrode sheet is obtained.

[0191] (3) Isolation film:

[0192] A 12 μm polyethylene film was used as the separator.

[0193] (4) Preparation of electrolyte:

[0194] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0195] (5) Assembly of secondary batteries:

[0196] The positive electrode sheet and negative electrode sheet prepared as above are placed in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0197] Secondary battery performance test

[0198] (1) Test of the first coulombic efficiency of secondary batteries:

[0199] At 45°C, the secondary battery prepared in Example 1 was formed and charged at a constant current of 0.02C for 10 hours (record the charge capacity C0 at this time). At 25°C, the secondary battery was discharged at a constant current of 0.2C to 2.0V, and the discharge capacity D0 at this time was recorded. Then it was charged at a constant current of 0.33C to 3.8V, and then charged at a constant voltage to a current of 0.05C, and the charge capacity at this time was recorded as C1. Discharged at a constant current of 0.33C to 2.5V, stood for 5 minutes, discharged at a constant current of 0.33C to 2.0V, and then discharged at a constant current of 0.1C to 2.0V, and the discharge capacity at this time was recorded as D1.

[0200] The first coulombic efficiency (%) of the secondary battery = D1 / (C0-D0+C1).

[0201] (2) Testing of storage performance of secondary batteries:

[0202] At 25°C, the secondary battery prepared in Example 1 was charged to 3.8V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage. After standing for 5 minutes, the secondary battery was discharged to 2.0V at a constant current of 1C, and the discharge capacity at this time was recorded, which was the discharge capacity before storage.

[0203] At 25°C, the secondary battery prepared above was charged to 3.8V at a constant current of 1C, and then charged at a constant voltage to a current of 0.05C. The secondary battery was then stored in a 60°C constant temperature box for 200 days, and the secondary battery was discharged to 2.0V at a constant current of 1C, and the discharge capacity at this time was recorded, which was the discharge capacity after storage.

[0204] Capacity retention rate (%) of the secondary battery after storage at 60° C. for 200 days=discharge capacity after storage / discharge capacity before storage×100%.

[0205] Example 2

[0206] Artificial graphite was prepared by a preparation method similar to that of Example 1, and button cells and secondary batteries were assembled, with the only difference being that the precursor II was mixed with liquid asphalt having a coking value of 15% at a mass ratio of 100:4 in liquid phase.

[0207] The artificial graphite, button cell and secondary battery obtained in Example 2 were tested by the same testing method as in Example 1. The test results are shown in Tables 1-2 and 1-3.

[0208] Example 3

[0209] Artificial graphite was prepared by a preparation method similar to that of Example 1, and button cells and secondary batteries were assembled, with the only difference being that the precursor II was mixed with liquid asphalt having a coking value of 15% at a mass ratio of 100:1 in liquid phase.

[0210] The artificial graphite, button cell and secondary battery obtained in Example 3 were tested by the same testing method as in Example 1. The test results are shown in Tables 1-2 and 1-3.

[0211] Comparative Example 1

[0212] Artificial graphite was prepared by a preparation method similar to that of Example 1, and button cells and secondary batteries were assembled. The only difference was that the precursor II was directly graphitized at 3000° C. for 7 days, and then demagnetized and sieved to obtain artificial graphite.

[0213] The artificial graphite, button cell and secondary battery obtained in Comparative Example 1 were tested using the same testing method as in Example 1. The test results are shown in Tables 1-2 and 1-3.

[0214] Comparative Example 2

[0215] Artificial graphite is prepared by a preparation method similar to that of Comparative Example 1, and button batteries and secondary batteries are assembled, with the only difference being that the precursor II is graphitized at 3000°C for 7 days, and the graphitized product after demagnetization and screening is coated with liquid asphalt with a coking value of 15% in a mixing ratio of 100:2 by mass, and the coated material is carbonized at 1150°C for 2h to obtain artificial graphite with an amorphous carbon layer coated on the surface.

[0216] The artificial graphite obtained in Comparative Example 2 was tested by the same testing method as in Example 1. When the lattice spacing of the surface portion was tested by the same method as in Example 1, sampling was performed in the area in contact with Pt, and no obvious stripes were obtained after subsequent fast Fourier transform. Therefore, it was determined that the surface portion of the artificial graphite obtained in Comparative Example 2 was amorphous carbon.

[0217] Subsequently, the button cell and the secondary battery obtained in Comparative Example 2 were tested using the same testing method as in Example 1. The test results are shown in Tables 1-2 and 1-3.

[0218] Table 1-1

[0219]

[0220] Table 1-2

[0221]

[0222] Table 1-3

[0223] Serial number First coulombic efficiency (%) Storage at 60℃ for 200 days Capacity retention rate (%) Example 1 94.7% 88.2% Example 2 94.2% 86.4% Example 3 94.0% 85.5% Comparative Example 1 93.6% 84.5% Comparative Example 2 93.2% 84.2%

[0224] In Table 1-1, “ / ” indicates that no related items are added.

[0225] It can be seen from the data in Table 1-1 to Table 1-3 that, compared with Comparative Example 1 (no surface portion is provided in the artificial graphite) and Comparative Example 2 (the surface portion is amorphous carbon), Examples 1 to 3 can improve the first coulombic efficiency and storage performance of the battery.

[0226] Embodiment 4-6

[0227] Artificial graphite was prepared by a preparation method similar to that in Example 1, and button cells and secondary batteries were assembled. The only difference was that when preparing the artificial graphite, the type of carbon-containing additive was adjusted as shown in Table 2-1 below.

[0228] In addition, referring to the test method of Example 1, the artificial graphite, button cells and secondary batteries of Examples 4-6 were tested, and the test results are shown in Table 2-2.

[0229] Table 2-1

[0230]

[0231] Table 2-2

[0232]

[0233]

[0234] It can be seen from the data in Table 1-1, Table 1-2, Table 1-3, Table 2-1 and Table 2-2 that the use of the carbon-containing additives defined in the present application is beneficial to reducing the BET specific surface area of ​​artificial graphite, thereby further improving the first coulombic efficiency and storage performance of the secondary battery.

[0235] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: The invention comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises artificial graphite. The artificial graphite includes a surface portion and a central portion, the surface portion is continuously or discontinuously distributed in the central portion, the interplanar spacing D002 of the surface portion is greater than the interplanar spacing D002 of the central portion, wherein the interplanar spacing D002 is the interlayer spacing of the graphite 002 crystal plane.

2. The secondary battery according to claim 1, characterized in that: The interplanar spacing D002 of the surface portion is 0.345 nm to 0.355 nm.

3. The secondary battery according to claim 1 or 2, characterized in that: The interplanar spacing D002 of the central portion is 0.335 nm to 0.345 nm.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The artificial graphite satisfies at least one of the following: (1) The BET specific surface area of ​​the artificial graphite is 0.6 m 2 / g to 1.4m 2 / g; (2) I of the artificial graphite D / I G The value is 0.05 to 0.15, where I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at (3) The volume average particle size Dv50 of the artificial graphite is 12 μm to 22 μm; (4) The powder compaction density of the artificial graphite at 50000N is 1.93 g / cc to 2.15 g / cc; (5) The gram capacity of the artificial graphite is 355 mAh / g to 365 mAh / g.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The BET specific surface area of ​​the artificial graphite is 0.85 m 2 / g to 1.18m 2 / g.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The artificial graphite D / I G The values ​​range from 0.067 to 0.

087.

7. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 6.

8. An artificial graphite, characterized in that: The artificial graphite includes a surface portion and a central portion, the surface portion is continuously or discontinuously distributed in the central portion, the interplanar spacing D002 of the surface portion is greater than the interplanar spacing D002 of the central portion, wherein the interplanar spacing D002 is the interlayer spacing of the graphite 002 crystal plane.

9. The artificial graphite according to claim 8, characterized in that The interplanar spacing D002 of the surface portion is 0.345 nm to 0.355 nm.

10. The artificial graphite according to claim 8 or 9, characterized in that: The interplanar spacing D002 of the central portion is 0.335 nm to 0.345 nm.

11. The artificial graphite according to any one of claims 8 to 10, characterized in that: The artificial graphite satisfies at least one of the following: (1) The BET specific surface area of ​​the artificial graphite is 0.6 m 2 / g to 1.4m 2 / g; (2) I of the artificial graphite D / I G The value is 0.05 to 0.15, where I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at .

12. A method for preparing artificial graphite, characterized in that: include: Mixing a binder and an artificial graphite precursor, and then granulating the mixture to obtain a first mixture; performing a first heat treatment on the first mixture to obtain a second mixture; mixing the second mixture and a carbonaceous additive to obtain a third mixture; The third mixture is subjected to a second heat treatment to obtain artificial graphite, wherein the artificial graphite includes a surface portion and a central portion, wherein the surface portion is continuously or discontinuously distributed in the central portion, and the crystal plane spacing D002 of the surface portion is greater than the crystal plane spacing D002 of the central portion, wherein the crystal plane spacing D002 is the interlayer spacing of the graphite 002 crystal plane.

13. The preparation method according to claim 12, characterized in that: The artificial graphite precursor includes one or more of calcined coke, petroleum non-needle coke, petroleum needle coke, coal non-needle coke and coal needle coke.

14. The preparation method according to claim 12 or 13, characterized in that: The artificial graphite precursor includes calcined coke.

15. The preparation method according to any one of claims 12 to 14, characterized in that: The carbon-containing additive includes at least one of solid asphalt, liquid asphalt and polyacrylonitrile.

16. The preparation method according to any one of claims 12 to 15, characterized in that: The carbonaceous additive includes liquid asphalt.

17. The preparation method according to any one of claims 12 to 16, characterized in that: The coking value of the liquid asphalt is 10% to 20%.

18. The preparation method according to any one of claims 12 to 17, characterized in that: Compared with the mass of the artificial graphite precursor, the added amount of the carbon-containing additive is less than 10%.

19. The preparation method according to any one of claims 12 to 18, characterized in that: Compared with the mass of the artificial graphite precursor, the added amount of the carbon-containing additive is 0.5% to 6%.

20. The preparation method according to any one of claims 12 to 19, characterized in that: The first heat treatment includes a pre-carbonization treatment at 1000°C to 1500°C.

21. The preparation method according to any one of claims 12 to 20, characterized in that: The second heat treatment includes graphitization at 2800° C. to 3200° C.

Citation Information

Patent Citations

  • High-rate double-layer coated graphite negative electrode material, lithium ion battery and preparation method of high-rate double-layer coated graphite negative electrode material

    CN112421001A

  • Graphite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN117691091A

  • Graphite negative electrode active material and preparation method thereof, negative electrode plate, secondary battery and electric device

    CN119852340A

  • Negative electrode material for lithium ion secondary batteries, negative electrode for lithium ion secondary batteries, and lithium ion secondary battery

    WO2022264384A1

Cited By

  • Secondary battery, electrical device, artificial graphite, and preparation method therefor

    WO2026016589A1